Descrição de outras doenças sexualmente transmissíveis em pessoas infectadas pelo vírus da imunodeficiência humana do tipo 1 - MESQUITA, Francisco Carlos Lopes de (Universidade Federal do Pará, 2013)
Ninety patients seroreactive to HIV-1 were studied in order to describe the clinical manifestations of other sexually transmitted diseases as well as the demographic and behaviour factors associated to the HIV-1 infected and AIDS patients. The majority (83.3%) were males with a mean age of 31.4 years of age (range between 18 and 60 years) and a monthly family income for 79.5% of less than five mininum wages. At least one type of ilicit drug was used by 51.1% and 20.7% were intravenous drug users. Among them, 94.4% referred to a previous episode of a sexually transmitted disease. The subjects revealed that 41.6% were bisexuals, 38.2% heterosexuals and 20.2% were homosexuals. Approximately 51.1% of the bisexual subjects were intravenous drugs users and all referred to have had ano-rectal intercourse and were all positive for the presence of antibodies to Chlamydia. The mean age of the first sexual relation with penetration and the first episode of sexually transmitted disease were at 14.7% and 20.6% years of age, respectively. The vast majority (95.5%) of the subjects experienced multiple sexual partners before the knowledge of their HIV-l positive serology status. Among the 73.3% that referred a previous episode of sexually transmitted diseases, 82.2% also referred urethral discharge, syphilis and herpes simplex. At physical examination, 36.6% (33/90) presented urethral, anal and vaginal discharge and genital lesions such as discharges (51.1%), vesicles (18.1%), warts (18.1%), lymphadenopathy (18.1%), ulcers (12.1%) and papules (6%). Reaction to the VDRL and antibodies to Chlamydia were present in 13.7% and 96.4%, respectively. The vast majority referred ano-retal intercourse and previous episodes of sexually transmitted diseases.